The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1070/rc1998v067n05abeh000371
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of carbonyl compounds with α,β-unsaturated nitriles as a convenient pathway to carbo- and heterocycles

Abstract: Abstrad.We re-examine the so-called Nambu-Iona-Lasinio mechanism suggested by Song, Xu and Chin in breaking the supersymmetry in the Wess-Zumino model and show that this mechanism cannot be justified without assuming special effects behveen fermions. The fermion condensation suggested by them corresponds to an mstable vacumm configuration and as a result there is no fermion condensation and no supersymmetg breaking in the model they discuss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 129 publications
2
23
0
Order By: Relevance
“…Two recent reports on this subject are coincident with that proposal [257,258]. The conversion of the latter into substituted tetrahydropyridines and hexahydroquinolines [261][262][263][264] has been studied, but a number of questions remain open with respect to their structure and the direction of cyclization and alkylation [265]. Recently, the reaction of structural analogs-dimedone 240 and Meldrum's acid 461-with arylmethylenecyanothioacetamides, or aromatic aldehydes and cyanothioacetamide in the presence of secondary and tertiary amines, which produces the corresponding adducts of Michael addition has been described.…”
Section: Benzo Derivatives Of a Six-membered Ring With One Heteroatommentioning
confidence: 90%
See 1 more Smart Citation
“…Two recent reports on this subject are coincident with that proposal [257,258]. The conversion of the latter into substituted tetrahydropyridines and hexahydroquinolines [261][262][263][264] has been studied, but a number of questions remain open with respect to their structure and the direction of cyclization and alkylation [265]. Recently, the reaction of structural analogs-dimedone 240 and Meldrum's acid 461-with arylmethylenecyanothioacetamides, or aromatic aldehydes and cyanothioacetamide in the presence of secondary and tertiary amines, which produces the corresponding adducts of Michael addition has been described.…”
Section: Benzo Derivatives Of a Six-membered Ring With One Heteroatommentioning
confidence: 90%
“…It is known that reactions of compounds like 465 withbromoketones in DMF is accompanied by loss of Meldrum's acid and leads to the formation of substituted 2-thiazolylcyanoethylenes [265]. The results of interaction of Michael adducts with other alkyl halides have not been described.…”
Section: Benzo Derivatives Of a Six-membered Ring With One Heteroatommentioning
confidence: 99%
“…The resulting Michael adduct 11 then undergoes intramolecular cyclization producing the annelated iminopyran 12. Subsequent tautomeric [1,3]sigmatropic shift gives compound 8 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, the proposed mechanism is supported to some degree by isolation of analogous Michael adducts in the previously studied reaction of 4-hydroxycoumarin with arylidenecyanoacetamides. 3 On the other hand the three component reaction system of 4-hydroxycoumarin 1a, malononitrile 7 and substituted acetophenones 13(a-c) as the carbonyl compound under analogous conditions failed to produce any chromenes 15(a-c). It was found that the acetophenones 13(a-c) did react with malononitrile 7 to give unsaturated nitriles 14(a-c) but these did not undergo Michael reaction with the coumarin anion.…”
Section: Scheme 1 Mechanistic Pathway Towards 8(a-f)mentioning
confidence: 99%
“…However, this scheme is confirmed to some degree by isolation of analogous Michael adducts (Z = CSNH 2 ) in the previ ously studied reactions of 4 hydroxycoumarin with aryl idenecyanothioacetamides. 4 The three component reaction between coumarin 1, malononitrile 7a, and 1 benzyloxycarbonylpiperidin 4 one (13) as the carbonyl compound follows a different pathway. Under analogous conditions (see above), malo nonitrile 7a reacts with piperidin 4 one 13 to give unsat urated nitrile 14, which dimerizes into spiroheterocycle 15 rather than reacting with coumarin 1.…”
mentioning
confidence: 99%